Impact of Fine Sediment on TSS and Turbidity in Retention Structure - Tan, K.H.; Lai, S.H.; Ibrahim, S.; Sulaiman, N.M.N.; Sharifi, M.; Abe, S. (Scientific Research Publishing, 2014)
A study of the impact of fine sediment on various water quality parameters in retention structure such as sediment basin was conducted on stagnant and flowing condition. 7 water quality parameters (pH, TSS, turbidity, DO, BOD, COD, ammonium nitrogen) were measured and classified according to the Interim National Water Quality Standard (INWQS) for Malaysia. Results show higher fine sediment concentration causes higher TSS and turbidity. Besides, results show TSS and turbidity were influenced by soil type for the same amount of fine sediment. Soil Siri Rasau 1 showed highest TSS and turbidity value followed by soil Siri Bungor and soil alluvium. A good positive correlation of TSS versus turbidity and has been investigated in this study. Multiple nonlinear regression analysis revealed that parameter TSS is dependent on time, total soil mass, fine soil mass and flow rate.